An ontology based framework for creating purposeful online communities - Seyhan, Murat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
A purposeful community is a group of individuals whose actions help the community reach a set of goals. Such communities often use social network applications to communicate, coordinate, and track their activities. Twitter and Facebook are widely used for such purposes. These applications provide generic support for communication, whereas every community has different information and processing needs. For example, a community who is responding to a natural disaster will be concerned about the services and goods that need to reach victims or a community who is interested in animal rights will be interested in documenting various animals and making health services available. Clearly, the type of information for these communities is very different. Providing support for domain specific information and its processing usually involves custom applications by those who have the application building skills. Yet, many kinds of information could easily be defined by end users. If only, the means for specifying such needs were available. We propose an ontology-driven model for end users to create community-specific web applications that consume and generate Linked Data. Our model is based on the Purposeful Online Communities (POC) Core ontology, which models online communities in terms of community-specific information and activity structures. We demonstrate the use of this ontology with example communities.
Keywords: Social networks.; Multimedia systems.